Optical Quasi-Periodic Oscillation of Blazar PKS 1440-389 in the TESS Light Curve - Lu, He; Yi, Tingfeng; Tang, Yanke; Wang, Junjie; Zhang, Shun; Wang, Liang; Chen, Yutong; Shen, Yuncai; Dong, Liang; Zhang, Yangwei (Universe (Basel), 2024)
We report the results of time series analysis of blazar PKS 1440-389, observed by the Transiting Exoplanet Survey Satellite (TESS) in two sectors. We find that the source has a quasi-periodic oscillation (QPO) of about 3.1 days for sector 11 and around 3.7 days for sector 38 in the optical band. We use two methods to assess the QPO and its confidence level: Lomb–Scargle periodogram and weighted wavelet Z-transforms. We explore various potential explanations for these rapid quasi-periodic variations and propose that their source most likely resides within the innermost region of the accretion disk. Within this framework, we estimate the mass of the central black hole of this blazar. We obtain black hole masses of 6.65 × 108M⊙ (Schwarzschild black hole) and 4.22 × 109M⊙ (maximally rotating Kerr black hole), with a main period of 3.7 days. Finally, we utilize the kink instability model to explain the QPO.